Effect of Different Types of Denture Cleansers on Hardliner Surface Roughness - Nurul Ifadah; Rani Purba; Martha Mozartha (Indonesian Dental Association, 2022)
Introduction: Hard liner is a denture relining material which can be used directly at the chairside in brief time. The characteristic of the hardliner is its susceptibility towards porosity which consequently resulting biofilm accumulation and Candida albicans colonization. Thus, there is a need for denture cleaning. Alkaline peroxide is a type of denture cleanser which is widely used, but it could affect the physical properties of hard liner. One of the traditional ingredients that have the potential to be used as an alternative to denture cleanser is cinnamon. Objective: This study aimed to evaluate the effect of different types of denture cleansers on the surface roughness of hard liner. Method: Twelve cylindrical hard liner specimens (15mm x 10mm, ASTM: D-2240 64T) were divided into three groups: group I (immersed in distilled water), group II (immersed in alkaline peroxide) and group III (immersed in 1.5% extract cinnamon). All specimens were soaked for 15 minutes/day for 7 days. Surface roughness was measured using surface roughness tester (Handysurf E-MC-S24B Japan). Data were analysed using one-way ANOVA and post hoc Bonferroni (Î±=0.05). Results: The highest average of surface roughness was shown on specimens immersed in alkaline peroxide, followed by specimens immersed in 1.5% cinnamon extract and distilled water, respectively. There were a significant difference in surface roughness values in all groups (p<0.05). Conclusion: There is an effect of type of denture cleanser on the surface hardness of hard liner.